QUO VADIS EU ENVIRONMENTAL DIPLOMACY? - Ellya Dameria; Ivonne Easteria Riyadi (Sociae Polites, 2020)
Environmental issues should be a priority in the study of the current post-modern era of international relations. The after-effects of industrialization and technological progress have a very crucial impact on the global environment. Hence, we begin to examine the contemporary history of the efforts of the European countries as the first spearhead of the industrial revolution in dealing with the environmental crisis. The European Union is experiencing a lot of issues, commonly in the case of Environmental Diplomacy. Quo vadis is a Latin phrase meaning “Where are you going?”. From this term, it will be seen how the problems that occur as well as the future that will be confronted with the aid of the EU. EU used to be in conflict with countless events such as with the United States, China, Indonesia, and even had its very own members, specifically Britain. Keywords : Environmental Diplomacy, United States, Indonesia, European Union.